Pulmonary Tuberculosis and Microcytic Hypochromic Anemia in a 10- Year-Old Girl : A Family Medicine Approach - Wynne Deanita, Teresa; Nurrakhma Arum Kurnia, Siti; Rosita, Rita (Jurnal Ilmu Kedokteran Keluarga, 2026)
Pulmonary tuberculosis (TB) in children remains a significant public health problem, particularlyin low- and middle-income countries, where it often coexists with malnutrition and anemia. Thiscase report presents a 10-year-old girl with pulmonary TB and hypochromic microcytic anemia,exacerbated by poor nutritional intake, inadequate parenting supervision, exposure to cigarettesmoke, and suboptimal environmental conditions. The patient’s condition was complicated byrecurrent weakness, weight loss, and palpable lymphadenopathy. Laboratory results confirmedsevere anemia, while chest radiography revealed infiltrates consistent with TB. A holistic familymedicine assessment identified biomedical, psychosocial, environmental, and behavioral riskfactors. Comprehensive management included pharmacological therapy (first-line anti-tuberculosis drugs, iron, folic acid, multivitamins), nutritional interventions, health education, andfamily counseling. Family-focused and community-oriented strategies were emphasized,including TB contact screening, parental smoking cessation, and community health workerinvolvement. This case highlights the importance of holistic and comprehensive care in managingTB and comorbid anemia in children, underlining the role of family medicine in addressing bothclinical and contextual determinants of health.